CULTIVATION OF SHIMEJII ON ELEPHANT GRASS SUBSTRATE SUPPLEMENTED WITH DIFFERENT KINDS OF BRAN - DONINI, Lorena Pastorini; BERNARDI, Eduardo; MINOTTO, Elisandra; NASCIMENTO, José Soares do (Scientia Agraria, 2009)
The purpose of this work was to evaluate the cultivation of the strains of P. ostreatus in elephant grass substrate supplemented with different kinds of bran. The experiment consisted in the use elephant grass substrate supplemented with soy, wheat, rice or corn bran in concentrations of 0, 10 or 20% poured in flasks that were inoculated with spawns of BF24, DF33 and HF19 strains of P. ostreatus and incubated at room temperature (20 - 28 ºC). After the complete colonization of the substrate, the flasks were transferred to a fructification chamber with temperature between 20 and 26 ºC and average damp of 75 – 90%. The BF24 strain was found to be the most productive one in relation to the others and the supplementation of the elephant grass with wheat bran in concentrations of 10 and 20% favors higher productiveness and biological efficiency for the BF24, DF33 and HF19 strains of P. ostreatus.